Supercritical fluid extraction and quantification of chlorpyrifos insecticides in fresh vegetables by gas chromatography with electron capture detection (GC-ECD) - Rahman, Mohammad Arifur; Omar, Dzolkhifli; Sarker, Md. Zaidul Islam; Morshed, Md. Mahbub; Rashid, K. N. H. (Science Hub, 2010)
Supercritical Fluid Extraction (SFE) remains an attractive technique with great potentials for the selective determination of pesticides in complex matrices. A rapid and high percetage of recoveries extarction protocol of chlorpyrifos insecticides from fresh tomato, cucumber and potato vegetables matrixs using SC-CO2 was developed in this study. Chlorpyrifos recovered from tomato and cucumber with critical pressure, PC at 30 Ibs and critical temperature, TC 50°C. On the other hand, the recovery rate of similar insecticides from potato was 101% with PC at 30 Ibs and 55°C in TC. The recovery rate in tomato matrices was 90%; a cucumber matrix was 110% and 101% recovery from potato. The avg. retention time (tR) was 11.976 min of chlorpyrifos standard and similar tR was found in formulated of tomato and cucumber matrices. The lowest detectable limit (LDL) of chlorpyrifos insecticides was 0.02μg/mL with GC-ECD. Gas chromatography-electron capture detection (GC-ECD) temperature was of injection port and detector 280°C and 300°C, respectively and pressure was 18.5 psi with split less. However, the method is useful to recover non-polar insecticides from the fresh vegetable; thus, further research could be continued with cosolvents to recover the polar residues from different types of fresh vegetables.